Geospatial technique and multi-criteria evaluation to select suitable sites for groundwater recharge with reclaimed water in arid and semi-arid regions - Sinda Sifi; Abdelwaheb Aydi; Sabrine Zaghdoudi; Mohamed Gasmi; Hazem Ghassan Abdo (Water Cycle)
Water resources are suffering from shrinkage in quantity and quality as a result of unprecedented acceleration in population growth, urbanization, irrigation, agricultural, industrial activities and incessantly changing weather patterns. The use of reclaimed water as an alternative for groundwater recharge is an increasing practice worldwide, notably in arid and semi-arid countries like Tunisia where water scarcity is becoming more severe. In this study, geospatial technique and multi-criteria evaluation were combined to pinpoint an appropriate site for aquifer recharge with reclaimed water (ARrew) in Menzel Bourguiba in the Bizerte region, Northeastern Tunisia. Fifteen constraints and five factors clustered in two main objectives (environmental and economic) were chosen based on credible references, previous literature and expert knowledge to achieve the goal of this study. The Boolean approach was applied to exclude the unsuitable area for aquifer recharge. The fuzzy logic was used to standardize factors between zero and ten. Then, a relative weight was assigned to each criterion using the analytical hierarchy process (AHP) method. Then, the Weighted Linear combination (WLC) approach was used, and the final map of site suitability for ARrew was prepared. The results showed that twelve candidate sites were suitable for ARrew. The selected sites are outranked using the ELECTRE III method. The findings are directly applicable to similar regions, enabling the development of adaptable recharge strategies for broader impact. This work can be considered a promising tool for hydrologists in selecting suitable sites for ARrew, ensuring the availability of groundwater resources and sustainability.